The relationship between personality, season, and wounding receipt in zoo‐housed Japanese macaques (Macaca fuscata): A multi‐institutional study. Issue 12 (21st September 2021) - Doelling, Christina R.; Cronin, Katherine A.; Ross, Stephen R.; Hopper, Lydia M.
Abstract: It is important to those managing Japanese macaques ( Macaca fuscata ) in captive settings to understand predictors of wounding. While studies have demonstrated that season (breeding or nonbreeding) and sex predict rates of wounding received by zoo‐housed Japanese macaques, we investigated whether individual differences in personality ratings also might explain some of the observed interindividual variance in wounding. Such patterns were previously observed in rhesus macaques ( M. mulatta ), such that individuals rated higher on Anxiety and Confidence received greater wounding. Here, we collected wounding data over 24 months on 48 Japanese macaques from eight AZA‐accredited zoos. Each macaque was also rated by keepers using a 26‐item personality questionnaire. Principle components analysis of these ratings revealed four personality components: Openness, Friendliness, Dominance, and Anxiety/Reactivity. The model with the best fit revealed an interaction effect between season (breeding vs. nonbreeding) and the personality component Friendliness, such that individuals rated higher on Friendliness incurred fewer wounds in the nonbreeding season. The second‐best model revealed both a main effect of the season as well as an interaction effect between season and Openness, such that macaques rated higher in Openness received more wounds in the nonbreeding season than those rated lower in Openness. Thus, as with rhesus macaques, personality mediated wounding receipt rate in Japanese macaques, although different personality components explained interindividual variance in wounding for these two species. These differences likely reflect species differences in behavior and personality structure, as well as the influence of differing management practices, highlighting the importance of species‐specific approaches for captive primate care and welfare. This study provides further support for understanding primate personality to create individualized strategies for their care. Highlights: Predictors of the wounding receipt rate of 48 zoo‐housed macaques living in eight accredited zoos were examined. Wounding rates were mediated by interaction effects between the macaques' personality ratings and season. The macaques received more wounds during the breeding season, as compared to the nonbreeding season. Higher ratings on Friendliness were associated with the receipt of significantly fewer wounds received, but only in the nonbreeding season. Higher ratings on Openness were associated with the receipt of significantly more wounds received, but only in the nonbreeding season.